A 3-in-1 Polymeric Micelle Nanocontainer For Poorly Water-Soluble Drugs - Shin, Ho Chul (Mol Pharm, 2011)
Poly(ethylene glycol)-block-poly(d,l lactic acid) (PEG-b-PLA) micelles have a proven capacity for drug solubilization and have entered phase III clinical trials as a substitute for Cremophor EL in the delivery of paclitaxel in cancer therapy. PEG-b-PLA is less toxic than Cremophor EL, enabling a doubling of paclitaxel dose in clinical trials. We show that PEG-b-PLA micelles act as a 3-in-1 nanocontainer for paclitaxel, 17-allylamino-17-desmethoxygeldanamycin (17-AAG), and rapamycin for multiple drug solubilization. 3-in-1 PEG-b-PLA micelles were ca. 40 nm in diameter; dissolved paclitaxel, 17-AAG, and rapamycin in water at 9.0 mg/mL; and were stable for 24 hrs at 25°C. The half-life for in vitro drug release (t(1/2)) for 3-in-1 PEG-b-PLA micelles was 1-15 hrs under sink conditions and increased in the order of 17-AAG, paclitaxel, and rapamycin. The t(1/2) values correlated with log P(o/w) values, implicating a diffusion-controlled mechanism for drug release. The IC(50) value of 3-in-1 PEG-b-PLA micelles for MCF-7 and 4T1 breast cancer cell lines was 114 ± 10 and 25 ± 1 nM, respectively; combination index (CI) analysis showed that 3-in-1 PEG-b-PLA micelles exert strong synergy in MCF-7 and 4T1 breast cancer cell lines. Notably, concurrent intravenous (IV) injection of paclitaxel, 17-AAG, and rapamycin using 3-in-1 PEG-b-PLA micelles was well-tolerated by FVB albino mice. Collectively, these results suggest that PEG-b-PLA micelles carrying paclitaxel, 17-AAG, and rapamycin will provide a simple yet safe and an efficacious 3-in-1 nanomedicine for cancer therapy.